The constitutional interpretation - Gonzales Ojeda, Magdiel (2018)
If, from the formal and material point of view, a law was well drafted, its application would soon become effective and in that way the legal rule could be freed from the usual problems of interpretation. The constitutional interpretation configures all aspects where the law, on the other hand, when it becomes ambiguous and imprecise, then its interpretation becomes imperative. The constitutional interpretation, although it admits the fictionism that transposes the positivism, does not leave for that reason that the judicial activity is exempted of performing interpretative activity at the moment in which the law shows flaquezas by its generality and imprecision. In this essay, using a territory populated with topics and renewed arguments based on principles, the reader is offered guidelines to control the work that should be done by the judge, demanding knowledge that may limit his subjectivity in order to give him greater certainty to your decision. Hence the importance of constitutional interpretation that seeks to find solutions to specific issues through the use of a repertoire of topoi revealed by judicial experience.